2008
DOI: 10.1080/02699050802189727
|View full text |Cite
|
Sign up to set email alerts
|

Time to wake-up: Sleep problems and daytime sleepiness in long-term stroke survivors

Abstract: Background and purpose: In work with chronic stroke patients the authors observed that patients frequently appear sleepy and often comment on their poor sleep. Sleep difficulties are frequently reported and indeed clinically recognized in the acute phase post-stroke, but little is known about the sleep and daytime sleepiness of chronic stroke patients with sustained disabilities. The latter, however, deserves clarification because sleep is a critical modulator of health, daytime performance and wellbeing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 30 publications
2
60
2
4
Order By: Relevance
“…59 Hypersomnia and excessive daytime sleepiness are observed in 27% of patients, 59 whereas insomnia occurs in 57% of patients in the early months after stroke. 60 PSF is associated with sleep disturbances 21,26,31,35,50,[61][62][63] and daytime sleepiness 46,[63][64][65] in many studies, but these associations have not been consistently demonstrated. 20,24,49 The role of sleep disturbances as they pertain to PSF thus remains uncertain.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…59 Hypersomnia and excessive daytime sleepiness are observed in 27% of patients, 59 whereas insomnia occurs in 57% of patients in the early months after stroke. 60 PSF is associated with sleep disturbances 21,26,31,35,50,[61][62][63] and daytime sleepiness 46,[63][64][65] in many studies, but these associations have not been consistently demonstrated. 20,24,49 The role of sleep disturbances as they pertain to PSF thus remains uncertain.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…Therefore, it is unlikely that EDS in the sub-acute phase of stroke is because of a disrupted arousal system in the brain. Considering a previous report that reports that patients with fatigue due to chronic brain injury use compensatory strategies such as napping [32] , our patients may also have had EDS due to fatigue. This is also supported by our further analysis that patients with EDS took frequent naps, but they did not sleep longer at night nor report problems related to sleep terminaQuality of sleep at 3 months post stroke, n (%) 79 tion in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Another study carried out in 20 stroke survivors showed that 45% of these patients had experienced an increase in sleep latency although total sleep duration and efficiency were within normal values. 22 No abnormal sleep patterns have been found in patients with acute-phase hemispheric CVA compared to sleep patterns in control subjects. 23 However, a study of patients with subarachnoid haemorrhage (SAH) revealed that 34% of patients reported severe sleep problems.…”
Section: Sleep Architecture After Acute Strokementioning
confidence: 97%
“…This suggests that EDS in patients with CVA may arise independently from any nocturnal sleep disorders. 22 The pathophysiogenesis of EDS after stroke remains unknown, but it could be related to diffuse cortical dysfunction, especially in cases of SAH. 24 The above statement is supported by a case of histologically confirmed cortical laminar necrosis in which the polysomnographic study showed absence of slow waves and spikes during sleep (stage N2) and loss of ultradian organisation of sleep.…”
Section: Hypersomnias Of Central Origin Excessive Daytime Sleepiness mentioning
confidence: 99%